KERUSAKAN LINGKUNGAN: EPISTEMOLOGI SAINS ISLAM DAN TANGGUNG JAWAB MANUSIA - Mangunjaya, Fachruddin (TEOLOGIA, 2015)
Abstract: This article examines the challenges of environmental degradation and arguing to retun back to the Quran as a search of epistemological foundation of science and a necessary strong foundation in managing the balance of carrying for the earth and environmental crisis. This study also explores the principles of Islamic in view of the environmental approach such as the understanding keywords about the God creation (Ilm-al-Khalq), which can be laid as foundations such as tawá¸¥Ä«d, which encourage the belief that the only the Creator with all power single, the khalifah (caliph) that empasis on man responsibility, mÄ«zÄn which refers to maintaining a balance and keeping the fitrah as ordered of (human) nature in order to maintain the patterns of life and the integrity of Gods creation. Â  Abstrak: Artikel ini menguji tantangan-tantangan degradasi lingkungan dan mengajukan pendapat untuk kembali kepada al-Quran sebagai sebuah cara mencari dasar epistemologi sains dan sebuah dasar yang kuat dalam mengelola keseimbangan bagi bumi dan krisis lingkungan. Studi ini mengeksplorasi prinsip-prinsip Islam dalam memandang terhadap pendekatan lingkungan seperti adanya pemahaman kata-kata kunci tentang ciptaan Tuhan (âIlm al-Khalq), yang bisa ditempatkan sebagai dasar-dasar, yang mendorong keimanan sehingga hanya ada Sang Pencipta dengan kekuatan yang tunggal, sang khalifah yang menekankan pada tanggung jawab manusia, mÄ«zÄn yang merujuk pada mempertahankan keseimbangan pola-pola kehidupan dan integritas makhluk Tuhan. Â  Keywords: Islamic epistemology, science, lingkungan, khalÄ«fah, mÄ«zÄn.